Mortality Review of Children Admitted in Pediatric Intensive Care Unit Over One Year in a Tertiary Care Hospital - Shrestha, Pun Narayan; Agrawal, Sumit; R C, Kosh Raj; Joshi, Prakash; Rayamajhi, Ajit (Birat Journal of Health Sciences, 2021)
Introduction: Childhood mortality is still high in developing countries. This can be reduced with good preventive and curative services especially with critical care. The treatment of critically ill children must be focused for better outcome. The pediatrics deaths audit and review provide feedback to health workers and to the institution. The outcome measures of critical care medicine include mortality, morbidity and disability rate. Objectives: The aim of this study is to review the causes and mode of death in children and length of PICU (pediatric intensive care unit) stay. Methodology: A retrospective study was conducted of the patients who were admitted and died within the period of 16 July 2019 to 15 July, 2020 at PICU of Kanti Children Hospital (KCH). Variables recorded were patient's demography, diagnosis, co- morbidities, complications, length of PICU stay (LOS), mode and time of death. Data were tabulated into MS Excel and analyzed using SPSS version 23. Result: Out of 718 admitted children, 99 (13.78%) died with male to female ratio of 1.8:1. The maximum death (75%) was observed in less than five year of age and most of them were from outside the Kathmandu valley. The leading causes of death were pneumonia (28%), sepsis (20%) and congenital heart diseases (21%). The common complications seen were disseminated intravascular coagulation (DIC), multi- organ dysfunction syndrome (MODS), acute kidney injury (AKI) (5.1 %) and acute respiratory distress syndrome (ARDS) (6.1%) and co- morbidities were congenital heart disease (CHD) (18.2%) and global developmental delay (GDD) (9.1%). Mechanical ventilation was needed in 80.8%. Most of the cases (86%) died despite active treatment and (75%) during off hours (4pm-9am). Conclusion: Pneumonia, sepsis and CHD were the main reason of death and most of them were from outside the valley.